2022
DOI: 10.1155/2022/7735046
|View full text |Cite|
|
Sign up to set email alerts
|

Study on the Quality Analysis and Improvement of Tennis Teaching under the Internet System

Abstract: Improving the quality of tennis teaching and learning is an important part of the modernization of education in China. The limitations of traditional tennis teaching quality evaluation methods have made them controversial, and it is crucial to improve the scientific, rational, and timely evaluation of tenn is teaching quality. Therefore, it is necessary to establish a scientific and rational quality evaluation model for tennis education to evaluate the quality of tennis education. Based on the principle of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In particular, fuzzy math has shown a great deal of potential as a strategy for researching and improving physical education curricula (L. Zhao et al, 2021). Fuzzy mathematics, which has its roots in fuzzy logic and fuzzy set theory, offers a framework that is elastic and adaptive, making it suitable for dealing with the ambiguity and complexity of situations such as learning a new sport, for example (Zhang, 2022). The use of fuzzy mathematics in the development of educational systems for a range of sports has been the subject of a number of studies, which have shown that this methodology is effective in improving educational practices (Pan, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In particular, fuzzy math has shown a great deal of potential as a strategy for researching and improving physical education curricula (L. Zhao et al, 2021). Fuzzy mathematics, which has its roots in fuzzy logic and fuzzy set theory, offers a framework that is elastic and adaptive, making it suitable for dealing with the ambiguity and complexity of situations such as learning a new sport, for example (Zhang, 2022). The use of fuzzy mathematics in the development of educational systems for a range of sports has been the subject of a number of studies, which have shown that this methodology is effective in improving educational practices (Pan, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%